The minimum wage, informal pay and tax enforcement - Anikó Bíró; Daniel Prinz; László Sándor (Institute for Fiscal Studies (IFS), 2021)
We study the taxation of the minimum wage in an environment with imperfect enforcement and informality. We leverage an increase in the audit threat for earnings below a reporting threshold at twice the minimum wage in Hungary and estimate reporting and employment responses with administrative panel data. Using bunching estimators and difference-in-differences methods, we show that a substantial share of those who report earning the minimum wage earn at least the same amount off the books. When enforcement is imperfect, a taxed minimum wage serves as a backstop on underreporting and recovers some revenue but also increases informality.
Keywords: 330